Determinants of Emotional and Hedonic Factors in Unplanned Buying Behavior among Shopee Consumers in East Java - Ana Fitriyatul Bilgies; Sukesi Sukesi; JFX. Susanto Soekiman; Aminullah Assagaf; Armanu Armanu (LPPM Universitas PGRI Sumatera Barat, 2022)
This study aims to examine the influence of Sales Promotion, Paylater Facility, Shopping Lifestyle, and Price on Positive Emotion, Hedonic Consumption, and Impulse Buying among Shopee app consumers in East Java. The phenomenon of increasing impulsive buying behavior in e-commerce is an important issue in understanding modern digital consumer behavior. This study uses a quantitative approach with the Partial Least Square–Structural Equation Modeling (PLS-SEM) method to analyze the relationship between variables based on data collected from 140 active Shopee user respondents in East Java. The results of the study indicate that sales promotions, paylater facilities, shopping lifestyle, and price significantly influence consumers' positive emotions. Furthermore, these four variables were also shown to significantly influence hedonic consumption and impulse buying. Furthermore, positive emotions and hedonic consumption were shown to be important determinants in increasing impulse buying among Shopee consumers. This means that attractive sales promotions, easy paylater facilities, a high-quality shopping lifestyle, and appropriate price perceptions simultaneously encourage positive emotions, hedonic consumption behavior, and impulsive buying decisions. The implications of this research suggest that e-commerce players need to continue developing emotion-based digital marketing strategies. Shopee and similar platforms are advised to focus innovation on personalized promotions, increased transaction convenience, and enjoyable shopping experiences to boost consumer loyalty and impulse buying behavior.